DNA sequences at the ends of the genome of bacteriophage Mu essential for transposition. - Groenen, M A (1985)
We have determined the minimal DNA sequences at the ends of the genome of bacteriophage Mu that are required for its transposition. A mini-Mu was constructed on a multicopy plasmid that enabled the manipulation of the DNA sequences at its ends without affecting the genes essential for transposition. The genes A and B, which were cloned outside the ends of the mini-Mu on the same plasmid, were both needed for optimal transposition. In our experimental system the predominant end products of the transposition are cointegrates both in the presence and in the absence of B. Two regions ending approximately 25 and 160 bp from the left end and one ending approximately 50 bp from the right end appear to be essential for optimal transposition. Overlapping with these regions, a 22-base-pair sequence was recognized with the consensus Y-G-T-T-C-A-Y-T-N-N-A-A-R-Y-R-C-G-A-A-A-A, where Y and R represent any pyrimidine and purine, respectively. At the left end these sequences occur as direct repeats; at the right end this sequence is inverted with respect to those at the left end.